Integration of Cultural and Ecological Aspects in the Selection of Sustainable Materials for Traditional Balinese Architecture - Utami, Ni Wayan Ardiarani; Adhika, I Made; Dwijendra, Ngakan Ketut Acwin; Putra, I Dewa Gede Agung Diasana (ASTONJADRO, 2025)
Traditional Balinese architecture has a deep cultural value that is reflected in the use of locally-based materials that are in harmony with the philosophy of Tri Hita Karana and the principles of Asta Kosala Kosali. However, in the era of modernization, there has been a shift in the use of materials from local to industrial materials that are more accessible but have a higher environmental impact. This article examines the integration of cultural and ecological aspects in selecting sustainable materials for traditional Balinese architecture using a multi-criteria approach. The research method used is multi-criteria decision analysis (MCDA) and life cycle assessment (LCA) to compare sustainability parameters such as carbon footprint, material resilience, and local community involvement in the material production process. The study results show that the use of local materials such as bamboo, coconut wood, and natural stone has a higher sustainability value than industrial materials. This study offers policy-based solutions to improve the use of environmentally friendly materials while maintaining Balinese cultural values. This study is expected to be the basis for designing sustainable architecture policies that consider ecological and cultural aspects in a balanced manner.